2004
DOI: 10.1152/ajpcell.00231.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Na+-K+-ATPase α2-subunit isoform modulates contractility in the perinatal mouse diaphragm

Abstract: This study uses genetically altered mice to examine the contribution of the Na(+)-K(+)-ATPase alpha2 catalytic subunit to resting potential, excitability, and contractility of the perinatal diaphragm. The alpha2 protein is reduced by 38% in alpha2-heterozygous and absent in alpha2-knockout mice, and alpha1-isoform is upregulated 1.9-fold in alpha2-knockout. Resting potentials are depolarized by 0.8-4.0 mV in heterozygous and knockout mice. Action potential threshold, overshoot, and duration are normal. Spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 58 publications
8
37
0
Order By: Relevance
“…On the basis of these data, it was proposed that the ␣2 isoform mediates positive cardiac inotropy, whereas the ␣1 isoform mediates the toxic effects of cardiac glycosides. A number of studies re-enforced the importance of the ␣2 isoform in the regulation of Ca 2ϩ transients during contraction (7)(8)(9)12). Also, we confirmed that the ␣2 isoform mediates the positive cardiac inotropy observed at low concentrations of ouabain, by comparing the effect of ouabain on cardiac contractility in wild type hearts expressing the ouabain-sensitive ␣2 isoform with that in hearts expressing a genetically modified, ouabain-resistant ␣2 isoform (13).…”
supporting
confidence: 70%
“…On the basis of these data, it was proposed that the ␣2 isoform mediates positive cardiac inotropy, whereas the ␣1 isoform mediates the toxic effects of cardiac glycosides. A number of studies re-enforced the importance of the ␣2 isoform in the regulation of Ca 2ϩ transients during contraction (7)(8)(9)12). Also, we confirmed that the ␣2 isoform mediates the positive cardiac inotropy observed at low concentrations of ouabain, by comparing the effect of ouabain on cardiac contractility in wild type hearts expressing the ouabain-sensitive ␣2 isoform with that in hearts expressing a genetically modified, ouabain-resistant ␣2 isoform (13).…”
supporting
confidence: 70%
“…Accordingly, we crossed NKA␣2-heterozygous (Atp1a2 ϩ/Ϫ ) mice into the NCX1 TG background. The gene for the ␣2 isoform of NKA is the predominant gene expressed in skeletal muscle (50), and it is tightly coupled to NCX activity (51). We observed that NCX1 TG Atp1a2 ϩ/Ϫ mice had increased central nucleation and increased serum CK levels compared with NCX1 TG mice, as well as more obvious histopathology at 3 months of age (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…There was no significant group effect between genotypes for either ␣1 (P Ͼ 0.23) or ␣2 (P Ͼ 0.14) isoform. ␣-Isoform expression was measured by Western blot analysis using ␣1-and ␣2-specific antibodies, as described previously (20,37). The ␣3 Na,K-ATPase isoform is not detected in this preparation (20).…”
Section: Nak-atpase Transport In Resting and Contracting Skeletal Mumentioning
confidence: 99%
“…␣-Isoform expression was measured by Western blot analysis using ␣1-and ␣2-specific antibodies, as described previously (20,37). The ␣3 Na,K-ATPase isoform is not detected in this preparation (20). and produces large changes in Na,K-ATPase transport (18).…”
Section: Nak-atpase Transport In Resting and Contracting Skeletal Mumentioning
confidence: 99%
See 1 more Smart Citation